Transcranial parenhymal sonography in the diagnosis of Parkinson's disease - Mijajlović Milija; Petrović Igor; Stojković Tanja; Svetel Marina; Stefanova Elka; Kostić Vladimir S. (Vojnosanitetski Pregled)
Bacground/Aim. Modern ultrasound systems allow highresolution transcranial sonography (TCS) of the brain structures. Enlargement of the echogenic signal (hyperechogenicity) of the substantia nigra (SN) has been reported as a highly characteristic finding in idiopathic Parkinson's disease (PD) and is thought to reflect increased amounts of iron, bound to proteins other than ferritin, in the SN in the course of neurodegeneration. The aim of our study was to investigate the prevalence of the SN hyperechogenicity in PD patients, as well as its possible clinical correlates. Methods. The study comprised 103 consecutive PD patients and 50 healthy age-matched controls. For TCS examination a color-coded, phased array ultrasound system equipped with a 2.5 MHz transducer was used (ESAOTE Technos MP, Italia). The examination was performed through a preauricular acoustic bone window with a penetration depth of 16 cm and a dynamic range of 45-50 dB. The SN was identified within the butterfly shaped structure of the mesencephalic brainstem, with scanning from both temporal windows. Results. The SN hyperechogenicity was identified in 95 out of 103 examined PD patients (92%), which was marked in 60 (63%), and moderate in 35 patients (37%). Median SN echogenic size was larger contralateral to the clinically more affected side of the body. Unilateral SN hyperechogenicity was also found in 5 out of 50 healthy controls (10%). No ventricular enlargements were notified in our study. Conclusion. Our study demonstrated SN hyperechogenicity in more than 90% of PD patients. In adult subjects without neurological symptoms, the TCS finding of at least unilaterally marked SN hyperechogenicity indicates a subclinical functional impairment of the nigrostriatal dopaminergic system. .